Efficient and Color‐Tunable Dual‐Mode Afterglow from Large‐Area and Flexible Polymer‐Based Transparent Films for Anti‐Counterfeiting and Information Encryption. (5th April 2022) - Yang, Yifan; Liang, Yaohui; Zheng, Yitao; Li, Jian‐An; Wu, Shiying; Zhang, Huaqing; Huang, Tepeng; Luo, Suilian; Liu, Cong; Shi, Guang; Sun, Fengqiang; Chi, Zhenguo; et al.
Abstract: It remains a great challenge to develop polymer‐based materials with efficient and color‐tunable organic afterglow. Two indolocarbazole derivatives IaCzA and IbCzA have been synthesized and doped into poly(vinyl alcohol) (PVA) matrices. It is found that the resulting films can produce unique dual‐mode afterglow, which is composed of persistent thermally activated delayed fluorescence and ultralong organic phosphorescence. Besides, the IbCzA‐doped PVA film exhibits intense blue afterglow with Φ afterglow and τ afterglow up to 19.8 % and 1.81 s, respectively, representing state‐of‐the‐art dual‐mode organic afterglow performance. Moreover, our reported film has high flexibility, excellent transparency, and large‐area producibility; and the afterglow color of the film can be linearly tuned by temperature. Inspired by these distinctive properties, the PVA doped with IbCzA was employed as temperature‐sensitive security ink for anti‐counterfeiting and information encryption. Abstract : Two indolocarbazole derivatives IaCzA and IbCzA have been synthesized and doped into poly(vinyl alcohol) (PVA) matrices. It is found that the resulting films simultaneously produce persistent thermally activated delayed fluorescence and ultralong organic phosphorescence, and their afterglow colors can be linearly tuned by temperature. Besides, the IbCzA‐doped PVA film presents state‐of‐the‐art dual‐mode organic afterglow performance.